Dayah and Meunasah: Abu Teupin Raya is the reformer of Islamic Education in Aceh - Rizal, Muhammad; Iqbal, Muhammad (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
Abu Teupin Raya also called by Tengku H. Muhammad Ali Irsyad is the most influential Ulama in Aceh. In fact, he has contributed guarding in Islamic education such as establishing Dayah Darussa’adah and has been preserving dakwah on Islamic tradition with various writing on Islamic studies. Since 1967, according to the traditional view of dayah, he is keeping pesantren to develop with many models of Quantity and Quality education in Indonesia. In addition, he has 23 book papers with local language and Arabic handwriting. With the information above, this paper uses qualitative research methods and will be explored to the act Abu Teupin Raya to build dayah in Aceh where the legacy of the script Kitab Kuning is written for improving Islamic education in Aceh.